Aplicação de avaliação do risco ao efluente em estações convencionais de tratamento de água: identificação e caracterização de perigos - Debora Nery de Souza (2017)
Providing people with quality water and insignificant level of risk is the aim of a water treatment plant - WTP. Therefore, it is necessary that treatment plants exercise control over the quality of the water supply, following the current legislation guidelines. With this purpose, World Health Organization (WHO) proposed concepts and highlighted the importance of risk assessment throughout the water treatment process. In this study, risk aspects as related to the potential of noncompliance with the limits established in the current norm and compliance with the minimum sampling plan, are considered. Turbidity, free residual chlorine, total coliforms and E. coli are used as indicators, and are evaluated in WTP effluent in Espírito Santo, from January 2009 to December 2016. The methodology proposed by this study was based on the guidelines presented in the Manual of Procedures and Surveillance in Environmental Health Related to Water Quality for Human Consumption and in WHO's Guide to Drinking Water Quality. Compliance rates of the minimum sampling plan of the WTPs being studied varied from 321.9% for total coliforms and null values for turbidity and free residual chlorine. None of the stations presented simultaneous compliance for turbidity parameters, free residue and total coliforms. Similar results were obtained for the standards of potability required by current regulations: none of the companies presented total compliance for all four criteria simultaneously. Highlighting the turbidity parameter, whose maximum value was changed from 1.0 to 0.5 uT by Ordinance No. 2914/2011, adequacy to the potability standards was not verified in 10 of the 12 stations. Among the Risk analysis, four WTPs presented risk Low, seven presented risk Medium and one, WTP 06, presented risk High.